2023
DOI: 10.1039/d2tc04946e
|View full text |Cite
|
Sign up to set email alerts
|

Tough hydrogel–elastomer hybrids hydrophobically regulated by an MXene for motion monitoring in harsh environments

Abstract: The hydrophobic encapsulation method is one of the common methods to ensure the regular operation of electronics underwater. However, the preparation of hydrogel underwater sensors by hydrophobic encapsulation still suffers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It was observed that the mechanical properties of SPBF36 and SPBF45 were significantly superior to those of other samples due to the presence of strain-induced crystallization (SIC) of polybutadiene. , For SPBF56 and SPBF63, however, the content of TFEMA with a long side chain was too high to generate sufficient SIC. Figure c presents a comparison of the tensile strength of reported elastomer materials with hydrophobic property in recent years. Among them, SPBF45 exhibited the best mechanical performance up to 20.2 MPa in this study. Figure S4 exhibits the details of the stress–strain curves within 5% strain, revealing that the Young’s modulus increased from 8.1 to 48.8 MPa with increasing TFEMA content, as shown in Figure d and Table .…”
Section: Resultsmentioning
confidence: 70%
“…It was observed that the mechanical properties of SPBF36 and SPBF45 were significantly superior to those of other samples due to the presence of strain-induced crystallization (SIC) of polybutadiene. , For SPBF56 and SPBF63, however, the content of TFEMA with a long side chain was too high to generate sufficient SIC. Figure c presents a comparison of the tensile strength of reported elastomer materials with hydrophobic property in recent years. Among them, SPBF45 exhibited the best mechanical performance up to 20.2 MPa in this study. Figure S4 exhibits the details of the stress–strain curves within 5% strain, revealing that the Young’s modulus increased from 8.1 to 48.8 MPa with increasing TFEMA content, as shown in Figure d and Table .…”
Section: Resultsmentioning
confidence: 70%
“…Our previous research focused on examining the role of MXene as physical crosslink points in MXene-hydrogel composites. 115 Recently, Li et al explored MXene-hydrogel composites with 1D flexible nanocellulose fibrils and 2D Ti 3 C 2 T x MXene, forming a layered structure with high ionotronic conductivity and mechanical strength. 116 An electrical soft actuator was fabricated, achieving significant reversible out-of-plane swelling (85% strain) with a low AE1 V voltage.…”
Section: Electrically Driven Hydrogel Compositesmentioning
confidence: 99%
“…Dai et al designed a hydrogel-elastomer hybrid for harsh environment sensing. 133 A dual-physically crosslinked hydrogel hydrophobically regulated by MXene with excellent anti-drying and anti-swelling properties was fabricated, and human thoracic breathing, pulse beats, and joint movements underwater could be monitored using the hybrid fiber sensor. Overall, these MXene-based hydrogel sensors show great potential in healthcare and medical applications, providing a good basis for practical applications and future commercialization.…”
Section: Applications Of Stimuli-responsive Mxene-based Hydrogelsmentioning
confidence: 99%